#TITLE_ALTERNATIVE# - SATYAGAMA (NIM 15109029) ; pembimbing : Dr. Deni Suwardhi, ST., MT, DILLAN
Digital Terrain Model (DTM) is the best method for representing three-dimensional landform for landscape structuring. In this research, UAV photogrammetry mapping technique used for DTM production. The resulting aerial photographs processed in two different ways, ie, automatically and manually. However, the results of automatic processing is DSM (Digital Surface Model) which still has the height of buildings and vegetation. To eliminate this, the filtering process is carried out using two different methods : simple morphological filter (SMRF) with MATLAB and DTM-Slope Based Filters with SAGA-GIS. Aerial photo processing is done manually with spotheighting techniques. DTM production (spotheighting) process is done with two different software namely Summit Evolution and Leica Photogrammetry Suite. In the automated processing with Agisoft Photoscan, an experiments is done by using 24 B GCP configuration, so not all measured GCP used as control point in the automatic aero triangulation process. On the 24 B configuration number of GCP that used as control points were 8 and the rest 9 GCP were used as checkpoint. The final results of this study are six different DTM (DTM SMRF, DTM SMRF 24 B, DTM Slope, DTM Slope 24 B, DTM Summit & DTM LPS) and the comparison (differencing) of the sixth DTM using surface-to-surface and point-to-point method. Analysis .By using DTM results from Summit Evolution processing (DTM Summit) as a reference, obtained an average elevation values difference between the DTM Summit with DTM SMRF by 6.154 m, DTM Summit with DTM SMRF 24 B by 3.317 m, DTM Summit with DTM Slope was 6.495 m, DTM Summit with DTM Slope 24 B was 4.576 m and DTM Summit with DTM LPS at 8.721 m.